A Trend analysis of frozen embryo transfer at Alhikmah fertility center, Addis Ababa, Ethiopia - Getachew, Sewit (Ethiopian Journal of Reproductive Health, 2023)
Background: In recent years, the use of frozen embryo transfers in Artificial reproductive technology has gradually increased, owing to improvements in laboratory techniques such as vitrification and blastocyst culture making pregnancy rates approaching those of fresh transfer cycles. Objective: The objective of this study is to determine the pregnancy rate after frozen embryo transfer, analyze the clinical factors that can potentially influence the result of pregnancy and identify patients who could benefit from this approach. Methods: A retrospective cross sectional study design was used to select patients that have undergone frozen embryo transfer from January 1, 2019- March 31, 2022 at Alhikmah fertility center, Addis Ababa, Ethiopia. Baseline data and pregnancy rate was collected, computed with SPSS version 24 for statistical associations and presented with tables. The primary outcome was a positive pregnancy test defined as serum ?-HCG level of >10mIU/ml. Result: A total of 180 frozen embryo transfers were done for 128 women over the study period and the pregnancy rate was 26.6%. The mean age of the patients was 31.88(± 5.04). Majority (45.3%) had tubal factor infertility. ? 13(median) oocytes were collected for 53.9%. A freeze-all technique was used in 46% of the patients and the rest had extra embryos. Age of the patient <35 and retrieval of oocytes above median had relation with positive pregnancy outcome. More importantly, freezing for risk of hyperstimulation and transfer of day 5embryos had a significant association with pregnancy with p-value <0.05. Conclusion: From this study, we’ve seen promising pregnancy rate after frozen embryo transfer in patients with age group <35 and those having ?13 oocyte. In addition, we can conclude that freezing for women at risk of hyperstimulation and transferring day 5embryos leads to a positive pregnancy result. However, since this is a retrospective study, we suggest a prospective comparative study to be done in the future for better recommendation. Key words: frozen embryo transfer, pregnancy rate, outcome predictors, assisted reproductive technology